p-Pyridinyl oxime carbamates: synthesis, DNA binding, DNA photocleaving activity and theoretical photodegradation studies - Gritzapis, Panagiotis S.; Varras, Panayiotis C.; Andreou, Nikolaos-Panagiotis; Katsani, Katerina R.; Dafnopoulos, Konstantinos; Psomas, George; Peitsinis, Zisis V.; Koumbis, Alexandros E.; Fylaktakidou, Konstantina C. (Beilstein Journal of Organic Chemistry, 2020)
A number of p-pyridinyl oxime carbamate derivatives were prepared upon the reaction of the corresponding oximes with isocyanates. These novel compounds reacted photochemically in the presence of supercoiled plasmid DNA. Structure–activity relationship (SAR) studies revealed that the substituent on the imine group was not affecting the extend of the DNA damage, whereas the substituent of the carbamate group was critical, with the halogenated derivatives to be able to cause extensive single and double stranded DNA cleavages, acting as “synthetic nucleases”, independently of oxygen and pH. Calf thymus–DNA affinity studies showed a good-to-excellent affinity of selected both active and non-active derivatives. Preliminary theoretical studies were performed, in an effort to explain the reasons why some derivatives cause photocleavage and some others not, which were experimentally verified using triplet state activators and quenchers. These theoretical studies seem to allow the prediction of the activity of derivatives able to pass intersystem crossing to their triplet energy state and thus create radicals able to damage DNA. With this study, it is shown that oxime carbamate derivatives have the potential to act as novel effective photobase generating DNA-photocleavers, and are proposed as new leads for “on demand” biotechnological applications in drug discovery and medicine.
Keywords: DNA binding; DNA photocleavage; N–O homolysis; oxime carbamates; photocleavage agents